Teori Konseling Adlerian: Pandangan Tentang Hakikat Manusia Dengan Melihat Persepsi Subjektif dan Pola Kepribadian Ditinjau Oleh Urutan Kelahiran Dan Sibling Relationship - Bakhrudin All Habsy; Shofiyyah Qurrotul A’yun; Devi Damayanti; Fhito Atma Khumariaksy (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2024)
Adlerian counseling is a counseling approach developed by psychologist Alfred Adler which focuses on understanding individuals as part of a social and cultural context, as well as individual motivation to achieve life goals, by paying attention to power dynamics, motivation, self-confidence and interpersonal relationships in an effort to help individuals overcome problems and grow personally. The method used in this research is qualitative with a type of literature study. Literature study is solving problems by tracing sources of writing that has been written before. The sources obtained are used as literature study material and are arranged according to the rules of scientific writing. The aim of this research is to find out in depth about Adlerian counseling theory. The research findings discuss: (1) Views on human nature, (2) Subjective perceptions of reality, (3) Unity and patterns of human personality, (4) Social interests and feelings of community, (5) Birth order and sibling relationships.